The personality of stealth democrats: how traits shape attitudes towards expert-based governments - Ackermann, Maya; Ackermann, Kathrin; Freitag, Markus (West European politics, 2019)
While some scholars call for mechanisms to give citizens a greater voice in politics, others critically question the demand for more citizen participation. Rather, they find that the people do not want to be involved in politics and prefer independent experts to make political decisions. This perspective is captured by Hibbing and Theiss-Morse in their concept of stealth democracy. They describe stealth democrats as people who think that political debates are unnecessary or who naturally avoid all sorts of conflict. Especially the latter argument points to a potential psychological underpinning of stealth attitudes, which forms the starting point of the investigation here. This article evaluates the personality of stealth democrats and makes use of a well-known concept to capture personality traits, the ‘Big Five’ model. Analysing unique survey data from Switzerland, the results reveal significant relationships between personality traits such as conscientiousness, agreeableness, and neuroticism and stealth attitudes.
Published online: 07 Nov 2018
Gesehen am 14.04.2021